The role of knowledge economy in African business - Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2015)
This paper assesses the role knowledge economy (KE) in African business in 53 countries for the period 1996-2010. The four KE components of the World Bank are employed, notably: education, innovation, economic incentives & institutional regime and information & communication technology. The business indicators are classified into: starting, doing and ending business. Principal components analysis and panel instrumental variable fixed effects approaches are employed as empirical strategies. The findings which are broadly consistent with intuition and the predictions of economic theory suggest that KE policies will substantially boost the starting and doing of business in Africa. This is relevant in fighting unemployment and improving African competitiveness in global value chains. Policy implications for the relevance of each specific KE dimension in African business are discussed with particular emphasis on the theoretical underpinnings of the study. The investigation is original in its contribution at the same time to the scarce literature on African KE and the growing challenges of improving the business climate of the continent by means of KE.
Keywords: L59; O10; O30; O20; O55; 330; Knowledge Economy; Doing business; Development; Africa